THE LIMITS OF CRIMINALIZATION AND THE PRINCIPLE OF LEGALITY IN BLANKET ECONOMIC CRIMINAL OFFENSES: Whoever does not deal in good faith shall be punished! - Todorović, Aleksandar D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
This paper analyzes the practice of the Supreme Court (of Cassation) in cases where this court ruled on the limits of criminalization in blanket economic criminal offenses. For many years, defense attorneys in these cases have presented the Supreme Court with the issue of distinguishing between criminal and civil liability, as well as the issue of determining the specific act of commission alleged against suspects when they are prosecuted for blanket economic criminal offenses. Attempts by defense attorneys to obtain an accurate response from the Supreme Court regarding the distinction between criminal and civil liability, and to receive an answer about the extent to which the act of commission of these blanket offenses can be expanded, have not borne fruit. By comparing the positions taken by the Supreme Court in its decisions with the positions of legal theory regarding the significance, nature, and content of guarantees arising from the principle of legality, and further comparing them with the positions taken on this issue by the European Court of Human Rights, this paper concludes that the principle of legality in blanket economic criminal offenses has been completely undermined. It also suggests that suspects are subjected to entirely arbitrary prosecution for these criminal offenses. The flexibility of judicial interpretation in determining the boundaries of liability in blanket economic criminal offenses has gone so far that it can truly be said that courts in Serbia, in these cases, are guided by the principle of good faith rather than the principle of legality, hence the paper's subtitle.
Keywords: limits of criminalization, principle of legality, blanket criminal offenses, abuse of position of a responsible person